Carotid atherosclerosis and its relationship to coronary heart disease and stroke risk in patients with type 2 diabetes mellitus. Issue 39 (September 2017) - Wu, Yan; He, Jie; Sun, Xue; Zhao, Yi-Ming; Lou, Han-Yu; Ji, Xiao-li; Pang, Xiao-Hong; Shan, Li-Zhen; Kang, Ying-Xiu; Xu, Jun; Zhang, Song-Zhao; Wang, Yong-Jian; et al.
Abstract : Abstract: Carotid atherosclerosis (CA) and carotid plaque (CP) are highly correlated with cardiovascular disease. We aimed to determine the prevalence of CA and CP and their relationship with 10-year risks of stroke and coronary heart disease (CHD) in type 2 diabetes mellitus (T2DM). We studied 1584 T2DM patients aged 20 years and older. CA and CP were detected using ultrasonography. Ten-year stroke and CHD risk were determined using the United Kingdom Prospective Diabetes Study (UKPDS) risk engine. The prevalence of CA and CP increased gradually with age. Men had a higher prevalence of CA than women (CA: 58.18% vs 51.54%, P < .01). The 10-year CHD risk (27.9% vs 15.4%, P < .001) and stroke risk (15.2% vs 5.70%, P < .001) were higher in patients with CA than that of those without CA. Compared with patients without CA, the odds ratios (ORs) of CHD in CA and CP group were 4.47 and 10.78 for men, and 4.19 and 5.20 for women, respectively; in the case of stroke, the OR in CA and CP group were 8.83 and 12.07 for men, and 4.35 and 4.90 for women, respectively ( P < .001 for all). Multivariate binary logistic regression analysis showed that CA was an independent risk factor for CHD [OR = 2.66, 95% confidence interval (95% CI), 2.05–3.46, P < .001] and stroke (OR = 3.11, 95% CI, 2.38–4.07, P < .001). CA and CP were prevalent in patients with T2DM and positively correlated with 10-year CHD and stroke risk. CA was an independent risk factor for 10-year CHD risk.